Non-invasive in vivo study of morphology and mechanical properties of the median nerve - Xu, Ruixia; Ren, Lei; Zhang, Xiao; Qian, Zhihui; Wu, Jianan; Liu, Jing; Li, Ying; Ren, Luquan (Frontiers in Bioengineering and Biotechnology, 2024)
Current literature studied the median nerve (MN) at specific locations during joint motions. As only a few particular parts of the nerve are depicted, the relevant information available is limited. This experiment investigated the morphological and biomechanical properties of the MN. The effects of the shoulder and wrist motions on MN were explored as well. Eight young healthy females were tested with 2-dimensional ultrasound and SWE. The morphological and biomechanical properties were examined in limb position 1, with the wrist at the neutral position, the elbow extended at 180°, and the shoulder abducted at 60°. And the experiment assessed the differences among the wrist, forearm, elbow, and upper arm with Friedman's test and Bonferroni post hoc analysis. Two groups of limb positions were designed to explore the effects of shoulder movements (shoulder abducted at 90° and 120°) and wrist movements (wrist extended at 45°, flexed at 45°) on the thickness and Young's modulus. Differences among the distributions of five limb positions were tested as well. The ICC3, 1 for thickness and Young's modulus were 0.976 and 0.996. There were differences among the MN thicknesses of four arm locations in limb position 1, while Young's modulus was higher at the elbow and wrist than at the forearm and upper arm. Compared to limb position 1, only limb position 4 had an effect on MN thickness at the wrist. Both shoulder and wrist motions affected MN Young's modulus, and the stiffness variations at typical locations all showed a downward trend proximally in all. The distributions of MN thickness and Young's modulus showed fold lines patterns but differed at the wrist and the pronator teres. MN in the wrist is more susceptible to limb positions. And Young's modulus is sensitive to nerve changes and is more promising for the early diagnosis of neuropathy.